2021
DOI: 10.1111/ijcp.14244
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety during the COVID‐19 pandemic in Saudi Arabia: A cross‐sectional study

Abstract: Aims:The emergence of the COVID-19 global pandemic, with a high transmission and mortality rate, has created an extraordinary crisis worldwide. Such an unusual situation may have an undesirable impact on the mental health of individuals which, in turn, may influence their outcomes. This study aimed to explore the influence of the COVID-19 pandemic on the psychological disposition of residents of the Kingdom of Saudi Arabia. Methods:A cross-sectional study using an online survey was conducted in Saudi Arabia be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 36 publications
(71 reference statements)
2
42
1
2
Order By: Relevance
“…Studies in Australia have explored mental distress among medical students and found that there was a significantly higher incidence when compared to the general public [ 4 , 5 ]. Similarly, comparable findings were reported in different countries in Asia and Africa [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Previous studies conducted in Saudi Arabia (at Jizan University) and in Tanzania (in Dar Es Salaam) reported similar findings that 71.9% and 70.0% of the students have experienced mental distress, respectively [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Studies in Australia have explored mental distress among medical students and found that there was a significantly higher incidence when compared to the general public [ 4 , 5 ]. Similarly, comparable findings were reported in different countries in Asia and Africa [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Previous studies conducted in Saudi Arabia (at Jizan University) and in Tanzania (in Dar Es Salaam) reported similar findings that 71.9% and 70.0% of the students have experienced mental distress, respectively [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 89%
“…Due to the COVID-19 pandemic, which began in December 2019, multiple studies in the Middle East region (Jordan, Saudi Arabia, and Kuwait) have explored the social and mental burden of the COVID-19 pandemic on different sectors of the society, including university students, healthcare professionals and the general population [ 11 , 12 , 13 , 14 , 20 , 22 ]. A recent study in Saudi Arabia by Mohammed et al assessed the psychological conditions among university students during the pandemic and found that 26.9% had anxiety symptoms and 22.4% had stress symptoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted throughout the world have consistently found that the lethal spread of COVID-19 and its associated lockdowns have been associated with greater levels of anxiety and depression at the population level [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Several of these studies also noted greater perceived risk of contracting COVID-19 to be significantly associated with depression [53,56,58,59,62].…”
Section: Depressionmentioning
confidence: 97%
“…The findings of this survey demonstrate that more than a quarter of people in Kabul have experienced moderate to severe anxiety and that anxiety was more prevalent and severe among women than men. Studies conducted in China, 18 the Philippines, 11 and Saudi Arabia 19 reported similar findings, i.e. one-fourth of the participants reported to suffer from moderate to severe anxiety and female gender was affected more than male.…”
Section: Discussionmentioning
confidence: 55%